MODULAR BLOK DI RUANG BARISAN TERJUMLAH CESARO ORLICZ - Haryadi Haryadi (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2021)
On the Cesaro summable of orde-p sequence space, if the fuction is replaced by Orlicz function, it is not always easy to define norm in the space. In this paper, we study some properties of the Cesaro Orlicz summable sequence space. First, on the space we define a modular and its the luxemburg norm, and then some topological properties is explored. The results show that the sequence spaces is modular complete and nom complete. In addition, the space is a BK-space but not an AK-space.